Hyperscanning and Avoidance in Social Anxiety Disorder: The Visual Scanpath during Public Speaking - Chen, N.; Thomas, L.; Clarke, Patrick; Hicke, I.; Guastella, A. (Elsevier Ireland Ltd, 2015)
Social anxiety disorder (SAD) is a debilitating mental illness which is thought to be maintained in part by the aberrant attentional processing of socially relevant information. Critically however, research has not assessed whether such aberrant attentional processing occurs during social-evaluative contexts characteristically feared in SAD. The current study presents a novel approach for the assessment of the visuocognitive biases operating in SAD during a social-evaluative stressor. For this task, clinically socially anxious participants and controls were required to give a brief impromptu speech in front of a pre-recorded audience who intermittently displayed socially positive or threatening gestures. Participant gaze at the audience display was recorded throughout the speech. Socially anxious participants exhibited a significantly longer visual scanpath, relative to controls. In addition, socially anxious participants spent relatively longer time fixating at the non-social regions in between and around the confederates. The findings of the present study suggest that SAD is associated with hyperscanning and the attentional avoidance of social stimuli.